1996
DOI: 10.1177/07399863960181002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Susceptibility to Influence in Mexican American and Anglo Females

Abstract: To further evaluate the hypothesis of relatively greater susceptibility of influence in Mexican Americans, 3OAnglo and 30 Mexican American females were given the task of responding to a select set of Rorschach cards together with eitheranAnglo ora Mexican American confederate. All subjects observed the card and wrote down "three best responses," after which they showed each other their responses. Then subjects were asked to once more give two responses and "perhaps" include something that they had not seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…One clever psychological experiment sheds light on the role of differential power in producing conformity. Roll, McClelland, and Abel (1996) asked pairs of White and Mexican American women to record their top three responses to inkblots and to share their answers with their partners. After this, they asked each partner to add two more responses to their original list.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One clever psychological experiment sheds light on the role of differential power in producing conformity. Roll, McClelland, and Abel (1996) asked pairs of White and Mexican American women to record their top three responses to inkblots and to share their answers with their partners. After this, they asked each partner to add two more responses to their original list.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Exner (1993), in outlining the demography of the 700 adults he used as a "non-patient" normative sample for the Rorschach, indicated that only 43 of these individuals were Latina/o; again, it is unclear how many of these people were specifically Chicanas/os. Those few investigations that do exist specifically regarding Chicanas/os and the Rorschach possess a widely divergent set of research foci with no discernible program of research being conducted (e.g., Roll, McClelland, & Abel, 1996;Tori, 1989). Certain scholars (e.g., Costantino, Flanagan, & Malgady, 1995), however, have argued that the Exner scoring system has served to reduce the potential for cultural bias in this test, and because the Rorschach does not depend on an examinee's reading ability, it may be a more useful clinical assessment tool.…”
Section: Personality Assessment Issuesmentioning
confidence: 99%